Perancangan Sistem Manajemen Proyek Menggunakan Critical Path Method (CPM) di PT Adhi Putra Bangun Perkasa - Kania, R; Febriani, Reni; Maharani, Desti; Hendra, Yul; Rakhmat, Edy (Jurnal Ilmiah Sains dan Teknologi, 2025)
The reporting process is only through direct conversation, hampering evaluation, as there is no written record.. This research aims to design a management system, especially in project planning, that allows data entry, scheduling, and reporting in real time. The system design method used is the Waterfall Method with visual modelling using the Unified Modeling Language (UML). This system also utilizes the Critical Path Method (CPM) in helping project scheduling. The results of system testing using black box testing show that the output displayed is a web-based project management system that can perform needs planning and project reporting in real time. The conclusion obtained is that with the use of this system, recording project data no longer requires the use of paper, and data can be stored automatically, as well as project reporting that can be accessed in real time to facilitate project evaluation.